Ameliorasi Iklim melalui Zonasi Hutan Kota berdasarkan Peta Sebaran Polutan Udara - Siti Badriyah Rushayati; Endes N. Dahlan; Rachmad Hermawan (Forum Geografi, 2010)
Bandung regency is one of the cities with many environmental problems oc like other cities in Indonesia. These problems are the continues increasing the number and density of population, and the increasing increased industrial and transportation. On the other hard, the forest area and green open space in Bandung Regency continues to decline. This causes increased air pollution and air temperature. The problems can be sowed with micro climate reparation in Bandung regency using urban forest in order to improve the climate conditions (amelioration) efficiently and effectively.